Smart Sensor System of Soil Moisture Reading for Chilli Plant - Ahmad Rosly, Ahmad Ameerul Hakeem (IRC, 2019)
Gardening activities by chilli gardeners without the adequate supervising and provisioning of the soil nutrient and humidity will post risk for the condition of the chilli. Soil nutrient and humidity measurement is important for proper chilli plant growth and allows the gardeners to conduct effective fertilization. Gardeners need to alert for the amount of soil nutrients and the amount of watering needed for the chilli peppers to grow healthy. Nitrogen, Phosphorus and Potassium are the main key nutrients required for the plant growth. In the present work electrochemical sensor has been developed to determine the existing nutrients in the soil. The electrochemical sensor will determine the amount of existing nutrients based on the rate of ion absorption. Here the sensor along with the Arduino Microcontroller circuits is built to detect the deficient component of the soil and at the same time determine the humidity of the soil for effective watering of chillies.